Research on the Method of Equipment Maintenance Support Simulation Experiment Based on Exploratory Analysis - Peng, Ying Wu; Xiao, Ding; Li, Qing Min; Ruan, Min Zhi (Applied Mechanics and Materials, 2012)
Aiming at the character of complexity and uncertainty on equipment maintenance support system, a method named equipment maintenance support simulation experiment was brought forward to study maintenance support problem based on exploratory analysis, which was applied to support decision-making about uncertain support scheme alternatives. The main characteristics of EMSSE were analyzed in detail, and the working flow was designed. Finally, in an example about warship maintenance support system simulation model which was set up, the optimal scheme of various storehouse inventory distributions for spare part was gotten. The optimization result was consistent with the basic principle under the three-echelon maintenance support pattern, and validates that EMSSE is feasible and reasonable to supply uncertain decision assistance for equipment support.